Digestive Physiology of Octopus maya and O. mimus: Temporality of Digestion and Assimilation Processes - Gallardo, Pedro; Olivares, Alberto; Martínez-Yáñez, Rosario; Caamal-Monsreal, Claudia; Domingues, Pedro M.; Mascaró, Maite; Sánchez, Ariadna; Pascual, Cristina; Rosas, Carlos (Frontiers in Physiology, 2017)
Digestive physiology is one of the bottlenecks of octopus aquaculture. Although there are successful experimentally formulated feeds, knowledge of the digestive physiology of cephalopods is fragmented, and focused mainly on O. vulgaris. Considering that the digestive physiology could vary in tropical and sub-tropical species through temperature modulations of the digestive dynamics and nutritional requirements of different organisms, the present review was focused on the digestive physiology timing of O. maya and O. mimus, two promising aquaculture species living in tropical (22 - 30°C) and sub-tropical (15 - 24°C) ecosystems, respectively. We provide a detailed description of how soluble and complex nutrients are digested, absorbed and assimilated in these species, describing the digestive process and providing insight into how the environment can modulate the digestion and final use of nutrients for these and presumably other octopus species. To date, research on these octopus species has demonstrated that soluble protein and other nutrients flow through the digestive tract to the digestive gland in a similar manner in both species. However, differences in the use of nutrients were noted: in O. mimus, lipids were mobilized faster than protein, while in O. maya, the inverse process was observed, suggesting that lipid mobilization in species that live in relatively colder environments occurs differently to those in tropical ecosystems. Those differences are related to the particular adaptations of animals to their habitat, and indicate that this knowledge is important when formulating feed for octopus species.